Human, Transhuman, Posthuman Digital Archaeologies: An Introduction. (August 2019) - Díaz-Guardamino, Marta; Morgan, Colleen
Abstract : Current archaeological thought evokes a sparking Catherine wheel: spinning fireworks that detonate light, colour, and sound with every movement. These theoretical turns swirl alongside the ongoing development and adoption of scientific and digital techniques that have wide-ranging implications for archaeological practices and interpretations. Two particularly combustible developments are posthumanism and the ontological turn, which emerged within the broader humanities and social sciences. Posthumanism rejects human exceptionalism and seeks to de-centre humans in archaeological discourse and practice. Linked to this is the so-called 'ontological turn' (aka the 'material turn'), a shift away from framing archaeological research within a Western ontology and a movement beyond representationalism (i.e. focusing on things themselves rather than assuming that objects represent something else).